Assessing Drainage Performance of Turfgrass Rootzone in Sports Fields - Kesgin, Erdal; Gezici, Kadir; Tan, Remziye İlayda; Ağaçcıoğlu, Hayrullah; Karaağaçlı, Mustafa; Sağlam, Mehmet Turgut (Çanakkale Onsekiz Mart University, 2024)
Sports fields are used by many national and international organizations worldwide. For this reason, carefully studying the hydraulic and mechanical properties of sports field surfaces is a major engineering concern. This study aimed to increase sports turf's resilience and determine the mixing ratios and fertilizer doses in the rootzone in order to enable effective water drainage. In the field test, the mixture of 3 different soils (100% sand; 10% mixture + 90% sand; 20% mixture + 80% sand) was used for the mix of 70% ryegrass (Lolium perenne L.) and 30% bluegrass (Poa pratensis L.) in baskets with a size of 1.3 x 0.5 x 0.20 m. Moreover, the turfgrasses were grown through the application of two different doses (2.5 ml (A) and 3.0 ml (B)) of liquid humic acid named Run/Black Jak in addition to basic fertilization of 18-22-0 (slow-release fertilizer) + Nu Film spreader-sticker + 26-05-11 (slow-release fertilizer) + 9-9-9 (slow-release fertilizer containing +9% Fe). It was observed that 2 cm layer was formed under the turfgrass in rootzones with 80% sand + 20% sitl+clay mixture by slowing water drainage and negatively affecting infiltration, making it unsuitable for sports fields. Penetration, infiltration, and vane shear tests were performed, and it was determined that the best rootzone in terms of hydraulic and mechanical surface properties was the rootzone treatment formed with 10% silt-clay-organic mixture + 90% sand mixture.
Keywords: Sports Field; Rootzone; Turfgrass; Fertilizer; Drainage